Keutuhan Wacana pada Cerpen â€œAndai Jakarta Seperti Mata Kakakâ€ Karya Habiburrahman El Shirazy - Pramitasari, Afrinar (Universitas Suryakancana, 2023)
This article describes the use of cohesion and coherence in forming the discourse integrity of a short story. The data in this study are in the form of fragments of sentences in a short story entitled Â